Identificación de fitoconstituyentes y caracterización de flavonoides en las inflorescencias de Brassica oleracea L. var. Botrytis “coliflor” por Cromatografía líquida de alta resolución-Espectrometría de masas - González Siccha, Anabel Doris (2015)
Objective: To identify and characterize phytoconstituents flavonoids in the inflorescence of Brassica oleracea L. var. Botrytis "Cauliflower" by High performance liquid chromatography and Mass spectrometry. Biological material: Cauliflower collected in Simbal-Trujillo. Method: Qualitative identification of phytoconstituents present in the inflorescence by separation with increasing polarity solvents (ether, ethanol and water) by high performance liquid chromatography (HPLC) and mass spectra (MS / MS), characterization was performed on the products of flavonoids obtained after acid and alkaline hydrolysis. Results: The cauliflower inflorescences presented secondary metabolites as glucosinolates, steroids, saponins, tannins and flavonoids. In the analysis of HPLC-MS / MS was obtained retention time (Rt) of glycosylated flavonoids, identified as acylated derivatives ( R- CO-): Quercetin - 3 - diglucoside -7 - diglucoside ( Rt = 12.3 ) and quercetin -7 - glucoside ( Rt = 18.0 ) . In acid hydrolysis, kaempferol -3 - diglucoside -7 - glucoside ( Rt = 15.5) , produced kaempferol , aglycone and partial hydrolysis components as kaempferol -7 - glucoside ( Rt = 38.1 ) , kaempferol -3 - diglucoside (Rt = 34.9 ) and other di- kaempferol . With alkaline hydrolysis was obtained glycosylated flavonoids kaempferol -3 - diglucoside ( Rt = 34.9 ). Conclusion: The inflorescence of Brassica oleracea L. var. Botrytis "cauliflower" contains secondary metabolites as glucosinolates, steroids, saponins, tannins and flavonoids that were characterized as kaempherol and glucosyl quercetin being quercetin flavonoid presented in high amounts.